2022
DOI: 10.1155/2022/5108677
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Application of the Financial Early-Warning Model Based on the BP Neural Network

Abstract: In order to further improve the early-warning effect of enterprise financial crisis management and reduce the occurrence of enterprise financial crisis, by taking listed companies as examples and combining the operating conditions of listed companies, a financial crisis early-warning indicator system was built from five aspects of profitability, debt-paying ability, development ability, operation ability, and cash flow ability. In addition, a financial management early-warning model based on the BP neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The optimization of the BPNN model is the adjustment of specific parameters, such as adding hidden layers, adding single-layer neurons, increasing the maximum number of iterations, selecting different weight optimizers and activation functions, etc. In the early warning research on financial risks, Wang Ting et al constructed a variety of BPNN models to compare the results, and found that when the number of hidden layers increased from 1 to 3, the model learning accuracy and learning rate were more obvious improvement [12]. However, as the complexity of the hidden layer network increases, the learning efficiency of a single neuron node decreases, the network convergence speed decreases, and the error increases.…”
Section: Plos Onementioning
confidence: 99%
“…The optimization of the BPNN model is the adjustment of specific parameters, such as adding hidden layers, adding single-layer neurons, increasing the maximum number of iterations, selecting different weight optimizers and activation functions, etc. In the early warning research on financial risks, Wang Ting et al constructed a variety of BPNN models to compare the results, and found that when the number of hidden layers increased from 1 to 3, the model learning accuracy and learning rate were more obvious improvement [12]. However, as the complexity of the hidden layer network increases, the learning efficiency of a single neuron node decreases, the network convergence speed decreases, and the error increases.…”
Section: Plos Onementioning
confidence: 99%
“…Many scholars have conducted relevant research on this issue. Jiang et al [4] constructed a financial crisis warning indicator system from five aspects: profitability, debt repayment ability, development ability, operational ability, and cash flow ability, based on the operating conditions of listed companies. In addition, a financial management early warning model based on BP neural network algorithm has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning [3] has been applied to risk assessment [4], financial performance [5], fault network management [6], and other fields due to its ability to constantly learn and adapt to the development of enterprises.…”
Section: Introductionmentioning
confidence: 99%